Social and Psychological Adaptation of Children with Bronchial Asthma to Studying at School - S.N. Nedelskaya; Ye.V. Raskina; Ye.Yu. Akulova (Zaslavsky O.Yu., 2013)
This article represents the peculiarities of social and psychological adaptation to studying at school and the factors determining its success of children with bronchial asthma.